Financial Statement Training for Transparent and Accountable MSME Tax Reporting - Dian Sulistyorini Wulandari; Neng Asiah; Widiastuti Widiastuti; Elektra Naurah Salsabila (Lentera Ilmu Nusantara, 2026)
Micro, small, and medium enterprises continue to face challenges in financial management, particularly in preparing systematic financial statements and fulfilling tax obligations. These limitations often result in poor financial information quality and hinder effective business decision-making and tax compliance. This community service program aimed to improve the knowledge and skills of business owners in preparing financial statements as a basis for transparent and accountable tax reporting. The activity was conducted at Pelita Bangsa University on June 19, 2026, involving nine micro, small, and medium enterprise owners from Bekasi Regency. The program employed socialization, training sessions, hands-on financial statement preparation practices, tax reporting simulations, and mentoring in the use of simple financial recording technology. Evaluation was carried out through observation, interviews, and assessments conducted before and after the training. The results demonstrated an improvement in participants' understanding of transaction recording, financial statement preparation, and tax reporting procedures. Participants were also able to implement more structured financial recording practices and utilize simple technology to support business financial management. The program contributed positively to strengthening financial management capacity and increasing tax awareness among participants. Therefore, the training and mentoring activities can serve as an effective empowerment strategy to support more transparent, accountable, and sustainable business management practices.